THE RELATIONSHIP OF BONDING ATTACHMENT BETWEEN CHILDREN AND WORKING MOTHERS TOWARDS CHILDREN'S SOCIAL DEVELOPMENT AND INDEPENDENCE IN AL IZZAH KINDERGARTEN, MOJOKERTO - Lida Khalimatus Sadiya (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
The golden age period is a time of growth for children that occurs early in theirlives. During this period, children's growth and development occur veryrapidly. The foundation of children's growth and development during thegolden age is the family environment. The family is the primary environmentfor children's growth and development, shaping the good and bad aspects ofhuman personality. The role of mothers as parents is very important in forminga bonding attachment with children. Working mothers have less time withtheir children, which can affect their development. The treatment given byparents to children, whether in the form of affection or protection, accordingto the child's needs, will foster a bond. The purpose of this study was to analyzethe relationship between children's attachment to working mothers and thedevelopment of children's social independence at Al Izzah Kindergarten,Mojokerto. Quantitative research method with correlation research type, andits output is a Book with an ISBN and the Bershinta research journal. Basedon the results of the Pearson correlation test, which shows a correlationcoefficient of 0.537 and a significance level of 0.002 between the bondingattachment variable and social development and independence. Thesignificance value is less than 0.05; therefore, the Ha statement is accepted.The correlation value of 0.537, according to the correlation coefficient valueguidelines, indicates that the level of bonding attachment relationship betweenchildren and working mothers to social development and independence isincluded in the category of strong or high relationships.